A Retrospective Cohort Analysis of the Impact of Osteoarthritis on Disability Leave, Workers' Compensation Claims, and Healthcare Payments. Issue 12 (December 2021) - Thakkar, Sheena; Gifford, Brian; Sell, Heather; Schepman, Patricia; Robinson, Rebecca; Emir, Birol
Abstract : Objectives: Examine short-term disability (STD) and workers' compensation (WC) associated leave and wage replacements, and overall direct healthcare payments, among employees with osteoarthritis (OA) versus other chronically painful conditions; quantifying the impact of opioid use. Methods: Analysis of employees with more than or equal to two STD or WC claims for OA or pre-specified chronically painful conditions (control) in the IBM MarketScan Research Databases (2014 to 2017). Results: The OA cohort ( n  = 144, 355) had an estimated +1.2 STD days, +$152 STD payments, and +$1410 healthcare payments relative to the control cohort ( n  = 392, 639; P  < 0.001). WC days/payments were similar. Differences were partially driven by an association between opioid use, increased STD days/payments, and healthcare payments observed in pooled cohorts ( P  < 0.001). Conclusions: OA is associated with high STD days/payments and healthcare payments. Opioid use significantly contributes to these and this should be considered when choosing treatment. Abstract : Supplemental Digital Content is available in the text